A Study of Higher Education In Promoting Entrepreneurship In Madhya Pradesh: Examining the Role of Higher Education in Fostering Entrepreneurship in Madhya Pradesh (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Entrepreneurship is increasingly becoming avery relevant instrument in promoting economic growth in a country. Thus therole of higher education in promoting entrepreneurship in Madhya Pradesh isanalyzed in this context and its initiatives tend to explain a greater fall inunemployment levels as the nation gears up to invest more resources to turnMadhya Pradesh into an education hub. As entrepreneurs have the potential tocontribute much to society, researchers have tried to analyze entrepreneurs’personalities, skills and attitudes as well as the conditions that fosterentrepreneurship. The growing concern is how should the education institutions,particularly the higher education institutions, impart essentialentrepreneurial knowledge in the syllabus to equip future entrepreneurs withthe necessary skills – the so called “entrepreneurship education”.